Dialect in poetic translations: The case of Robert Burns' poetry in Russia and in Slovenia - Koletnik, Mihaela; Kaloh Vid, Natalia (Slavia Centralis, 2020)
The following paper examines the translation of the Scottish dialect in translations of the most famous Scottish poet, Robert Burns, into Russian and Slovene. Burns skilfully blended two linguistic traditions, vernacular Scottish and poetic Standard English, as the vehicle for poetic expression and became one of the first poets who established the significance of the Scottish dialect in literature. Burns’ poetry was translated into Russian by Samuil Marshak and into Slovene by Janez Menart. The results of the analysis show that Marshak omitted the dialect, markers of dialect and even unmarked linguistic expression to illustrate Burns’ characteristic blending of standard and non-standard speech. On the other hand, Menart often used non-standard and colloquial speech, implying the strategy of compensation.
Keywords: dialect; poetry; Robert Burns; Samuil Marshak; Janez Menart; translations